'And then again, I draw myself to the detail': Capturing experiential states in contemporary dance making through Expanded Fields. (19th May 2021) - Gibson, Ruth; Roche, Jenny
Abstract : This article illustrates the creative process and conceptual impetus for the development of the piece Expanded Fields ; a moving image installation with live performance, sound and virtual reality which was first presented in the Limerick City Gallery of Art in November 2019. The work highlights multiple filters through which the audience can encounter a piece of choreography, using a range of different media to invite the viewer into various degrees of proximity with the dancers in movement. Co-authors Ruth Gibson and Jenny Roche contextualise this collaboration undertaken with artist Bruno Martelli, composer Mel Mercier and the dancers, Kévin Coquelard, Henry Montes and Ursula Robb and articulate the application of process tools utilised to create the work. They draw on contributions from these collaborators on their experience of the making process as well as through materials produced by all involved in the development of the piece. The process tools included Micro-phenomenological Interviewing (MPI), movement initiated writing, Skinner Releasing Technique (SRT), motion capture, filmmaking and audio recordings. These methods were interwoven to reveal the tapestry of experiential layers that can be accessed when dancing or viewing a piece of dance. Placing them together within a gallery installation space and grounding these perspectives through episodic live performance, allowed the material to be encountered through various sensorial frames, from the immersive VR environment where the avatars of the dancers moved close to the viewer's body, to the foyer space where footage of the dancers from studio rehearsals could be viewed on tv screens. The article situates this creative work in relation to writing by theorists such as Teresa Brennan on affect and André Lepecki on Derrida's notion of the trace, alongside articulating potential alignments between SRT and MPI.